Análise do potencial fitorremediador e energético da biomassa das espécies Eichhornia crassipes (aguapé) e Pistia stratiotes (alface d’água) - Figueiredo, Sara Almeida de (2018)
The increased demand for natural resources, especially energy and water, has expanded the pressures on the environment. Several water treatment systems already exist or have been developed in order to reduce degradation of the aquatic ecosystem and facilitate the access to water reserves. There are, however, simple and natural techniques - such as phytoremediation - that use resources from the environment itself, which have proved to be important complements, or even alternatives, to the traditional water treatment systems and which have been considered to be quite effective and less expensive in comparison to the latter. Regarding that, this study intended to test the efficacy of the aquatic macrophytes species Eichhornia crassipes (water hyacinth) and Pistia stratiotes (water lettuce) in the phytoremediation process, through physicochemical analyzes of their culture water, obtained from the Jaguaribe River, located in the urban zone of João Pessoa - PB. In addition, it was evaluated the later use of these species as a source of energy through its burning in the form of briquettes, with analyzes of its immediate composition, calorific value and thermal analysis using Nitrogen atmosphere. The results indicate a high remedial capacity of the studied species, especially in terms of removal of total and thermotolerant coliforms, for which the efficiency reached was 99.72% for both species. Regarding their energetic characteristics, the values obtained for the calorific value, of 14,382 MJ/kg (water hyacinth) and 14.185 MJ/kg (water lettuce) are slightly below the European standard, but very close to the values observed for firewood, for which the aquatic biomass briquettes are considered as potential substitutes. The water hyacinth stood out with a calorific value and phytoremediation capacity slightly superior to those of the water lettuce, while the latter presented higher rate of biomass production. With these results it is possible to give adequate allocation to the surplus biomass from the Jaguaribe river’s eutrophication process, while producing energy in a clean and renewable way.